Evaluation of Olive Tree (Olea europaea L.) as A Biomonitor for Monitoring of Heavy Metal Pollution Caused by Traffic: Example of Artvin - Mustafa Umut Konanç (Doğal Afetler ve Çevre Dergisi)
In this study, the potential of using olive tree (Olea europaea L.) as a biomonitor was investigated in monitoring heavy metal concentrations caused by traffic density. For this reason, in soil, leaf, fruit and shell samples collected from regions where traffic density is different in the city center of Artvin province, Sulfur content (%) was determined by elemental analyzer and heavy metals (Cr, Ti, Fe, Ni, Co, Cu, Zn, Pb and Al) was determined by ICP-OES. The accuracy of the assay measurements was tested using LGC 6187 for soil samples and ERM-CD 281 for plant samples. The differences in the measurement results obtained were determined using the ANOVA test According to the results obtained; the highest sulfur value in soil, leaves, fruit and bark was determined at the points with the highest traffic density. Heavy metal concentrations for Cr, Ti, Fe, Ni, Co, Cu, Zn, Pb and Al elements in plant and soil samples were compared with other studies and regulations, and all metals were found to be within the limit values. In statistical studies, it has been determined that there is a significant difference between points at 95% confidence level. In addition, it has been found that metal concentrations of soil, leaves, fruits and bark decrease as they move away from traffic areas. This is an indication that olives can be used as biomonitors in detecting traffic pollution.